PENGARUH PENGGUNAAN PADLET TERHADAP PEMAHAMAN MATERI MATEMATIKA DI SMA SHALAHUDDIN KELAS X - Ashfiak, Roudotul; Fuat; Supriyo (IAIN Pontianak, 2025)
This research aims to analyze the effect of using the Padlet digital platform on understanding mathematics material in class X students at Salahuddin High School. In mathematics learning which is generally considered abstract, Padlet is expected to be able to increase students' understanding and activity through more interactive and visual media. The research method used is a mixed approach with data collection techniques in the form of pretest and posttest tests, perception questionnaires, observations and interviews which were carried out in October 2024. The results of the research show that learning using this padlet is less effective in improving understanding of mathematics material in a direct and structured manner. However, students showed a preference for using Padlet, which was considered more interesting because it provided interactive features such as collaboration, note sharing, and material visualization that motivated them to participate actively. Overall, Padlet increases student engagement in mathematics learning and encourages collaborative interaction. Based on these findings, it is recommended to combine other learning methods with the use of Padlet to maximize students' understanding and involvement in mathematics learning.